Cluster Preface: Biocatalysis - Hyster, Todd K. (Synlett, 2020)
Enzymes are valuable catalysts in chemical synthesis because they offer levels of efficiency and product selectivity that surpass what can be achieved using traditional catalytic strategies. This Cluster highlights advances in this important field, highlighting different ways in which biocatalysis can be used in organic chemistry.
Keywords: biocatalysis; catalysis; enzyme; asymmetric catalysis; carbene transfer; cycloaddition; cascade reactions; photochemistry